Pola Klientelisme dan Distribusi Akses SPPG dalam Program Makan Bergizi Gratis - Ibrahim Askar (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This article analyzes the practice of clientelism in the governance of the Free Nutritious Meals (Makan Bergizi Gratis, MBG) program, particularly through the distribution of access to the Nutritional Fulfillment Service Units (Satuan Pelayanan Pemenuhan Gizi, SPPG). The study employs a qualitative approach using document analysis of reports published by Indonesia Corruption Watch (ICW), Tempo, and other supporting documents. The analysis applies Kitschelt and Wilkinson’s (2007) citizen–politician linkages framework. The findings show that access to SPPG management is distributed selectively to actors with political ties to the government, including party cadres, 2024 presidential campaign volunteers, political elites, military, and police networks. This pattern reflects clientelistic practices through patronage distribution, loyalty targeting, and monitoring mechanisms based on political networks. The study also finds an absence of competency-based standards in selecting SPPG partners, resulting in governance that prioritizes political proximity over technical capacity. Consequently, the MBG program becomes vulnerable to conflicts of interest, rent-seeking practices, and public service failures, including cases of mass food poisoning among beneficiaries. The article concludes that the MBG program has the potential to function as a medium for consolidating political patronage in Indonesia’s post-2024 electoral landscape.